Electro-optical Effect of 4-n-alkyl-sulfanyl-4' isothiocyanate-biphenyl Liquid Crystal Homologous Series Under Terahertz Frequency: A Theoretical Approach - Kumar, Yogesh; Kumar, Narinder (UI Scholars Hub, 2023)
This work presented the electro-optical effect of the homologous series 4-n-alkyl-sulfanyl-4'-isothiocyanate-biphenyl (N1SC13H8-SH2n+1Cn) under an electric field with terahertz (THz) frequency. The increase in alkyl sulfanyl chain length reduces the birefringence but increases the order parameter in THz frequency. An inverse relationship exists between the birefringence and order parameter. Meanwhile, the increase in alkyl sulfanyl chain length increases the refractive index with an even–odd effect. Birefringence, refractive index, order parameter, and director angle show an even–odd effect in the THz frequency range. The calculation is performed between 1 and 1,200 THz frequency. The isothiocyanate stretching corresponding to infrared absorbance remains unchanged for the whole series, showing potential in filtering and sensing applications.